Streaming to Success: Amplifying Purchase Intentions Among Malaysian Consumers - Ai Y.J.; Kiat N.P.; Jin N.Y.; Toong T.H.; Sze C.C.; Yee L.J. (Universiti Putra Malaysia, 2025)
This research project explores the factors influencing consumers' purchase intention via live streaming in Malaysia, including trustworthiness, social influence, perceived ease of use, and attractiveness. The study utilized both primary and secondary data, with questionnaires administered through Google Forms to 207 respondents in the urban areas of Malaysia. This study used Smart PLS software (version 3.0), and the findings suggest that trustworthiness, peer or social influence, and perceived ease of use have a significant relationship with purchase intention via live streaming among consumers in Malaysia, whereas attractiveness does not support this hypothesis. The findings of this study can assist new startups and entrepreneurs in gaining a better understanding of the live-streaming selling concept using the Source Credibility Theory. ? International Journal of Economics and Management.